The choice modelling approach to environmental valuation - Bennett, Jeff; Blamey, Russell (Cheltenham, UK ; Northampton, MA, USA : E. Elgar, 2001)
Choice modeling is a technique that has recently emerged as a means of estimating the demand for environmental goods and the benefits and costs associated with them. This book shows that choice modeling offers considerable potential for the evaluation of environmental goods and services.
The book has general editors of the series different from the editors of the each title.
Includes bibliographical references (p. 243-259) and index.
osc 05/09/2016
Loans
Keywords: Environmental economics; Environmental policy; Environmental policy - evaluation; Environmental policy - cost